Biased effects of taxes and subsidies on portfolio choices - Hagen Ackermann; Martin Fochmann; Benedikt Mihm (Arbeitskreis Quantitative Steuerlehre (arqus), 2012)
We study how taxes and subsidies affect portfolio choices in a laboratory experiment. We find highly significant differences after intervention, even though the net income is identical in all our treatments and thus the decision pattern of investors should be constant. In particular, we observe that the willingness to invest in the risky asset decreases markedly when an income tax has to be paid or when a subsidy is paid. If we combine both a tax and a subsidy, this effect intensifies.
Keywords: C91; D14; H24; 330; tax perception; risk-taking behavior; portfolio choice; distorting taxation; tax; subsidy; behavioral economics